Targeting Microglia in Neuroinflammation: H3 Receptor Antagonists as a Novel Therapeutic Approach for Alzheimer's Disease, Parkinson's Disease, and Autism Spectrum Disorder - Shilu Deepa Thomas; Sabna Abdalla; Nermin Eissa; Amal Akour; Niraj Kumar Jha; Shreesh Ojha; Bassem Sadek (MDPI AG, 2024)
Histamine performs dual roles as an immune regulator and a neurotransmitter in the mammalian brain. The histaminergic system plays a vital role in the regulation of wakefulness, cognition, neuroinflammation, and neurogenesis that are substantially disrupted in various neurodegenerative and neurodevelopmental disorders. Histamine H3 receptor (H3R) antagonists and inverse agonists potentiate the endogenous release of brain histamine and have been shown to enhance cognitive abilities in animal models of several brain disorders. Microglial activation and subsequent neuroinflammation are implicated in impacting embryonic and adult neurogenesis, contributing to the development of Alzheimer's disease (AD), Parkinson's disease (PD), and autism spectrum disorder (ASD). Acknowledging the importance of microglia in both neuroinflammation and neurodevelopment, as well as their regulation by histamine, offers an intriguing therapeutic target for these disorders. The inhibition of brain H3Rs has been found to facilitate a shift from a proinflammatory M1 state to an anti-inflammatory M2 state, leading to a reduction in the activity of microglial cells. Also, pharmacological studies have demonstrated that H3R antagonists showed positive effects by reducing the proinflammatory biomarkers, suggesting their potential role in simultaneously modulating crucial brain neurotransmissions and signaling cascades such as the PI3K/AKT/GSK-3β pathway. In this review, we highlight the potential therapeutic role of the H3R antagonists in addressing the pathology and cognitive decline in brain disorders, e.g., AD, PD, and ASD, with an inflammatory component.